KARAWITAN WAYANG GOLEK MENAK YOGYAKARTA VERSI KI SUKARNO - Aji Santoso Nugroho (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2015)
The presentation of karawitan wayang Golek Menak Yogyakarta of Ki Sukarno style is notdifferent from karawitan Wayang Kulit Yogyakarta. Issues of this article include what thestructure, the form, garap, and the function of karawitan presented by Ki Sukarno is. Theresearch aims to describe the structure, the form, garap, and the function of karawitan presented by Ki Sukarno. Based on the qualitative approach through musicology analysis of garapkarawitan, the finding shows that there is a difference between the presentation of laya orrhythm and kendhangan pattern that is ater-ater of wayang movement, ater-ater of bukaplayonand suwuk playon. Laya or rhythm is used by referring to dance karawitan and kendhanganpattern for Wayang Golek Menak contains vocabularies of dance movements. The gending usedin Wayang Golek Menak has gending baku of Ketawang Gending Kabor Topeng, Ayak-ayakKembang Jeruk, Playon Kembang Jeruk, Playon Gegot, and Playon Gambuh. The function ofkarawitanWayangGolekMenak is as a sign of the scene changing, the scene nuance, the dramatic element, the character’s characteristic, and the characteristic of wayang movement. Thepresentation structure of Wayang Golek Menak Yogyakarta refers to the structure of WayangKulit Purwa Yogyakarta. The difference lies on the dance movements before the war and thescene of gecul war.Keywords: karawitan, wayang golek menak, structure, function.